Pengaruh Media Audio Visual Terhadap Hasi Belajar Shooting Sepakbola Di Kelas Vii Smp Negeri 2 Majalaya - Maulana, Aditya; Nugroho, Setio; -, Abduloh (Peneliti.net, 2023)
The purpose of making this thesis is for the purpose of knowing the Effect of Audio Visual Media on Learning Outcomes of Shooting Football for Grade VII Students of SMP Negeri 2 Majalaya. The problem of this study is the lack of students' ability to shoot soccer games, teachers are less creative in providing learning material. This research is a quantitative research using experimental methods and using a one group pretest-posttest design. The sampling technique uses purposive sampling. The instrument used is shooting skills in a soccer game. There are three stages in this study, namely pretest, treatment and posttest. Treatment was carried out fourteen times. From the results of the pretest and posttest there were 55.13 before being given treatment and 76.13 after being given treatment. A significant value was obtained from the results of the pretest, namely 0.187 while the value of the posttest was 0.192 from these results, it is said that both are normally distributed because the significant value is more than 5% or from 0.05